The E3 Ubiquitin Ligase TRIM11 Facilitates Gastric Cancer Progression by Activating the Wnt/β-Catenin Pathway via Destabilizing Axin1 Protein. (21st February 2022) - Zhou, Ling; Wang, Heng; Zhong, Min; Fang, Zhi; Le, Yi; Nie, Fengting; Zhou, Juanjuan; Xiong, Jianping; Xiang, Xiaojun; Fang, Ziling
Abstract : Background . Aberrant expression of tripartite motif 11 (TRIM11) and the Wnt/ β -catenin pathway are essential for facilitating tumorigenesis and progression in multiple types of cancer. Aim . To investigate the molecular changes linking the dysregulation of TRIM11 and Wnt/ β -catenin pathway activation in gastric cancer (GC) progression. Methods . The expression levels of TRIM11 were detected in GC tissues and cells by immunohistochemistry and western blotting. The role of TRIM11 in the growth, proliferation, and invasion of gastric cancer cells was observed by a series of cell functional experiments and further verified in vivo. Co-immunoprecipitation (Co-IP), immunofluorescence, cycloheximide, and western blotting assays and other experiments were conducted to explore the mechanisms of TRIM11 underlying the regulation of the Wnt/ β -catenin pathway. For further verification, rescue experiments were performed by cotransfection of TRIM11 and Axin1 siRNA in GC cells. Results . Using Co-IP assays, we identified TRIM11 as a potent binding partner of Axin1 in GC cells. Elevated TRIM11 levels were significantly correlated with unfavorable clinical outcomes and poor survival in patients with GC. In addition, TRIM11 promoted the cell proliferation and invasion capacities of GC cells in vitro and tumor growth in vivo. Mechanistic investigations revealed that TRIM11 destabilized Axin1 protein by interacting with Axin1, thus inducing the activation of the Wnt/ β -catenin pathway. Moreover, we found that the oncogenic effects of TRIM11 on GC cells were partly mediated by suppression of Axin1. Furthermore, the protein expression of TRIM11 and Axin1 was negatively correlated in GC tissues. Conclusion . Collectively, our findings not only establish a pivotal TRIM11-Axin1- β -catenin axis in driving GC progression but also indicate that TRIM11 serves as a valuable therapeutic target for the treatment of GC patients.